2009
DOI: 10.1136/qshc.2007.025486
|View full text |Cite
|
Sign up to set email alerts
|

Audit of the consultation process on general internal medicine services

Abstract: Should the United States require mandatory reporting of medical errors within the health care system? Many barriers to medical error reporting currently exist and have made it difficult to establish a nationwide reporting system. As such, individual states have begun to address this issue one state at a time. This article reviews the barriers to nationwide reporting, provides a brief historical perspective on quality initiatives including medical error reporting, examines what the individual states have initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…2,9,22 In particular, Chen et al identified variability in the use of medical consultants following specific surgical procedures, 22 whereas we studied inpatient consultation more generally across the full spectrum of inpatient conditions seen in the Medicare population. While our study confirms earlier findings that sicker and more complex patients receive more consultations, we also demonstrate that patient comorbidities and prior hospitalizations contribute little to explaining the use of consultation use during acute hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…2,9,22 In particular, Chen et al identified variability in the use of medical consultants following specific surgical procedures, 22 whereas we studied inpatient consultation more generally across the full spectrum of inpatient conditions seen in the Medicare population. While our study confirms earlier findings that sicker and more complex patients receive more consultations, we also demonstrate that patient comorbidities and prior hospitalizations contribute little to explaining the use of consultation use during acute hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…8e11 Lack of efficient information exchange continues to be a formidable problem with medical consultations, resulting in inefficiency and increased health care costs. 2,12,13 We addressed how preconsultation exchange may address some of these inefficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…In a few cases, subspecialists did not believe sufficient information was provided in the referral to make an informed decision. Both quality and quantity of information provided in referrals need further study; a recent study found that more than one in four referrals did not contain a clear clinical question 25 . Future work may need to focus on developing, adopting, and integrating referral criteria specific to the services receiving referrals and testing EHR-based referral templates that reflect such criteria.…”
Section: Discussionmentioning
confidence: 99%